Development and Control of a Switched Capacitor Multilevel Inverter - Safwan Mustafa; Adil Sarwar; Mohd Tariq; Shafiq Ahmad; Haitham A. Mahmoud (Energies, 2023)
This article offers a novel boost inverter construction with a Nine-level quadruple voltage boosting waveform. The primary drawback of conventional MLI is the need for a high voltage DC-DC converter to increase the voltage when using renewable energy sources. Consequently, the developed method, complete with a quadruple voltage boost ability, can alleviate that shortcoming by automatically increased the incoming voltage. A single DC source, two switching capacitors, and eleven switches are all that are used in the newly presented architecture. The voltage of the capacitor automatically balances. The switched capacitor MLI is distinguished by the fewer parts that are required and the substitution of a capacitor for a DC source. The switching capacitor has to be charged and discharged properly in order to produce the nine-level output voltage waveform. The SPSC unit makes these levels attainable. To achieve voltage boosting, switched capacitors are coupled in parallel and series in the conduction channel. The quality of this proposed topology has been analyzed through different parameters based on the components count, THD, and cost; the resulting efficiency reaches 97.85%. The switching order of the proposed method has been controlled by the Nearest Level Modulation Method (NLC). MATLAB and PLECS software were used to evaluate the constructed Nine-level converter.